2019
DOI: 10.2147/oarrr.s226695
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interstitial Lung Disease in Systemic Sclerosis: Focus on Early Detection and Intervention</p>

Abstract: Systemic sclerosis (SSc) is a progressive and often devastating disease characterized by autoimmune dysfunction, vasculopathy, and fibrosis. Interstitial lung disease (ILD) is identified in the majority of patients with SSc and is the leading cause of SSc-related mortality. Although clinical manifestations and ILD severity vary among patients, lung function typically declines to the greatest extent during the first 3–4 years after disease onset. We aim to provide an overview of SSc-associated ILD (SSc-ILD) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 177 publications
(172 reference statements)
1
36
0
1
Order By: Relevance
“…The most common histopathologic findings are nonspecific interstitial pneumonia (NSIP; ~ 78%) [ 5 ]. Managing SSc-ILD is challenging because of the great heterogeneity of its courses, which can be stable or slowly or quickly deteriorating [ 6 8 ], and the modest benefit of immunosuppressants [ 9 12 ]. The initiation of immunosuppressants for SSc-ILD is usually recommended and more efficient in patients with active and/or progressing ILD, currently evaluated by the extension observed in high-resolution computed scans (HRCTs) and the deterioration in pulmonary function tests (PFTs; i.e., forced vital capacity [FVC] and diffusing capacity for the lung of carbon monoxide [D LCO ]) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common histopathologic findings are nonspecific interstitial pneumonia (NSIP; ~ 78%) [ 5 ]. Managing SSc-ILD is challenging because of the great heterogeneity of its courses, which can be stable or slowly or quickly deteriorating [ 6 8 ], and the modest benefit of immunosuppressants [ 9 12 ]. The initiation of immunosuppressants for SSc-ILD is usually recommended and more efficient in patients with active and/or progressing ILD, currently evaluated by the extension observed in high-resolution computed scans (HRCTs) and the deterioration in pulmonary function tests (PFTs; i.e., forced vital capacity [FVC] and diffusing capacity for the lung of carbon monoxide [D LCO ]) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…FDG PET/CT could therefore be more sensitive than HRCT alone in detecting early ILD and could allow early detection of therapeutic response. Together, these results suggest a need to provide more data on FDG PET/CT findings in SSc, especially in SSc-ILD [ 8 ]. Additionally, FDG PET/CT findings in extrapulmonary regions of interests (ROIs) linked to SSc have been scarce [ 24 26 ], and no study has reported systematic analysis of FDG extrapulmonary uptake related to SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Als Risikofaktoren für die Entwicklung einer ILD konnten das Vorliegen einer dcSSc, männliches Geschlecht, Afro-karibische Eth nizität und der Nachweis von Topoisomerase I-Antikörpern (Scl-70-AK) sowie das Fehlen von Centromer-Antikörpern identifiziert wer den [1,7,8]. In der Lungenfunktionsdiagnostik sind eine Reduk tion der forcierten Vitalkapazität (FVC) und der Diffusionskapazität der Lunge für Kohlenmonoxid (DLCO) wegweisend für eine ILD [1].…”
Section: Interstitielle Lungenerkrankung Bei Systemischer Skleroseunclassified
“…In patients with long-standing stable disease or early nonprogressive disease, treatment is not always indicated, and the best option may be supportive care. 28…”
Section: Introductionmentioning
confidence: 99%